Situated Learning in a Korean Older Adults’ Computer Classroom: A Situated Activity and Participation in Communities of Practice - Young Sek Kim (Adult Education Research Conference, 2008)
This study revealed four aspects of the social context which were embedded in the Korean older adults’ computer learning in a classroom and the participants’ identity changes due to their participation in communities of practice.
Keywords: older adults’ computer learning; situated learning; and community of practice